A comparison of take-off dynamics during three different spikes, block and counter-movement jump in female volleyball players - Kabacinski, J.; Dworak, L. B.; Murawa, M.; Ostarello, J.; Rzepnicka, A.; Maczynski, J. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purpose of the study was to compare the take-off dynamics in counter-movement jump (CMJ), volleyball block and spikes.